Savings and Investment Pattern of School Teachers – A Study with Reference to Sivakasi Taluk, Tamil Nadu - Mathivannan, S.; Selvakumar, M. (Indian Journal of Finance, 2011)
Money is an inextricable part of our life. People toil to earn money to purchase a house, to marry off their children, to live and to eat. So, saving is necessary to survive. To Save means to put aside a portion of income, deferring its consumption until a future date. Saving means the total accumulated amount of income that is not spent on consumption.In economics, personal saving has been defined as personal disposable income minus personal consumption expenditure. Saving may take the form of increase in bank deposits, purchase of securities, or increased cash holdings. The extent to which individuals save is affected by their preference for future over present consumption, their expectations of future income and to some extent, by the rate of interest. Saving plays a vital role in building up the household economy as well as the national economy. Savings provide the financial security to savers. Hence, attractive saving devices are very much necessary to increase and channel the savings in developing countries. India is taking much effort in inculcating the saving habit among the people.In order to mobilize savings, the Government of India is issuing saving certificates, government bonds and securities carrying high rates of interest.